Hubungan Tingkat Pengetahuan dan Sikap K3 Pekerja dengan Kejadian Kecelakaan Kerja di Pabrik ES - Sesarina Rahma Yasinta; Sri Darnoto (JUKEJ : Jurnal Kesehatan Jompa, 2026)
The purpose of this study was to analyze the relationship between the level of knowledge and attitude of Occupational Safety and Health (OHS) with the incidence of work accidents among workers at the PMP Ponorogo Ice Factory. The research method used was quantitative observational with a cross-sectional design. The population in this study were all workers at the PMP Ponorogo Ice Factory with a sample of 82 respondents taken using the total sampling technique. The independent variables included the level of knowledge and attitude of OHS, while the dependent variable was the incidence of work accidents. Data collection was carried out using a questionnaire, then analyzed using the Chi-Square test and Odds Ratio (OR) calculation using SPSS software. The results showed a significant relationship between the level of knowledge and the incidence of work accidents (p = 0.007; OR = 0.28) and a very significant relationship between OHS attitudes and the incidence of work accidents (p = 0.000; OR = 0.14). The conclusion of this study is that good OHS knowledge and attitudes play an important role in reducing the risk of work accidents among workers, so that increased OHS training and supervision need to be carried out continuously.